Twenty-Sixth Annual Homecoming, Popes Chapel Methodist Church, October 3, 1982 - (:unkn) unknown (Pope's Chapel United Methodist Church (Wilkes County, Ga.))
Twenty-Sixth Annual Homecoming, Popes Chapel Methodist Church, October 3, 1982. Raymond H. Lowe, Pastor. Event program. Pope's Chapel First Methodist Church. Wilkes County, Georgia. United States.
1 electronic document. popes-chapel_program_19821003.pdf. 4 pages. 26202442 bytes (master).
Keywords: Church history; Congregational churches; Homecoming; Methodist Church--Anniversaries, etc.; Methodists; Pope's Chapel United Methodist Church (Wilkes County, Ga.); Programs (Publications); United Methodist Church (U.S.); Wilkes County (Ga.); Georgia; Asbury, Francis; Blackmon, Tom; Bohler, Clarence H.; Boyd, Fortson; Boyd, James W.; Boyd, John W.; Bufford, Ethell; Bufford, Evelyn; Bufford, Lois; Butler, Mae; Cash, M. T.; Chafin, Elizabeth; Chafin, Malcolm; Combs, Farmer; Combs, Hazel; Echols, James E.; Fortson, Benjamin Winn; Gilliland, Ann; Harris, Lundye; Heater, Troy; Humphries, Thomas; Irvin, Charles; Jones, Hayes; Landrum, John; Lowe, Raymond H.; Lowe, Raymond; Neal, Augustus A.; Norman, Horace; Norman, Nanci; Ogilvie, Hannah Rebecca; Pope, Henry; Sale, David; Satterfield, Walker; Smith, George; Suttles, Joyce; Wheatley, Elaine; Wolfe, Janelle S.; Wright, Charles